1972
DOI: 10.1002/pen.760120103
|View full text |Cite
|
Sign up to set email alerts
|

Solids conveying in screw extruders part I: A modified isothermal model

Abstract: An improved theoretical model was derived for the solids conveying zone of a plasticating extruder. The model makes possible calculations in variable channel depth section. It also allows for a bulk density which is a function of pressure and for the non‐isotropic pressure distribution in the solid plug. An expression for maximum flow rate was also derived. Results simulated by the model on a computer indicate the effect of variables on extruder performance. The power consumption terms in the solids conveying … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
28
0

Year Published

1985
1985
2019
2019

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 61 publications
(28 citation statements)
references
References 1 publication
0
28
0
Order By: Relevance
“…The routine starts by computing pressure at the base of the hopper. Then, one assumes the development of a nonisothermal drag flow of an elastic solid plug in the initial turns of the screw [29], with heat conduction and dissipation at all surfaces. When the material near to the barrel interface reaches its melting temperature, a melt film appears and a set of equations for the delay zone is solved [30].…”
Section: Flow Modelingmentioning
confidence: 99%
“…The routine starts by computing pressure at the base of the hopper. Then, one assumes the development of a nonisothermal drag flow of an elastic solid plug in the initial turns of the screw [29], with heat conduction and dissipation at all surfaces. When the material near to the barrel interface reaches its melting temperature, a melt film appears and a set of equations for the delay zone is solved [30].…”
Section: Flow Modelingmentioning
confidence: 99%
“…The mathematical model has been developed with the aid of Tadmor and Broyer's theory [6] for two-dimensional, non-isothermal, non-isotropic plug flow of solid material. The ratio of normal stresses for calculating the non-isotropic pressure distribution coefficients [7] has been taken to be 0.4 according to Schneider's theory [8]. Examples of temperature and pressure profiles are shown in figures 1 and 2.…”
Section: The Solids Conveying Zone (Scz)mentioning
confidence: 99%
“…Xia et al proved that interfacial adhesion between polypropylene and the carbon nanotubes was improved by mechanically induced chemical reactions, which favored the dispersion. Researchers also studied the solids conveying in single‐ and twin‐ screw extruder and found that the solids conveying section would determine the delivery capacity and contribute to understanding melting process . Thus for comprehensively evaluating the performance of a continuous mixer, it is important to investigate the mixing process of filler particles and polymer pellets in solids handling section.…”
Section: Introductionmentioning
confidence: 99%